2019
DOI: 10.1007/s42770-019-00172-5
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth promoting and antifungal activity in endophytic Bacillus strains from pearl millet (Pennisetum glaucum)

Abstract: Bacterial endophytes are well known inhabitants of living plant system and perform important assignments in maintaining plant growth and health. Currently, limited reports are available on the endophytes of pearl millet (Pennisetum glaucum) reflecting antagonistic and plant growth promoting (PGP) attributes. Therefore, the major objectives of current investigation were to identify antagonistic strains of endophytic Bacillus from pearl millet and further illustrate their PGP capabilities. In this study, 19 endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 86 publications
5
31
0
Order By: Relevance
“…The findings of this study were supported by Kushwaha et al [24]. They described the PCR based amplification of antibiotic peptide related genes, including ItuD, BmyC, and srfA, from the 19 Bacillus endophytic bacterial strains with their biocontrol character in pearl millet cereal crop [24]. Moreover, Xu et al (2019) also published similar results related to functional biosynthesis antibiotic-related genes, such as PKSI, NRPS, ItuD, SrfC, and Sfp, by PCR from 33 different endophytic bacterial species, where 26 isolates from Bacillus ssp., showed antifungal activities against different phytopathogens of the mulberry plant respectively [25].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The findings of this study were supported by Kushwaha et al [24]. They described the PCR based amplification of antibiotic peptide related genes, including ItuD, BmyC, and srfA, from the 19 Bacillus endophytic bacterial strains with their biocontrol character in pearl millet cereal crop [24]. Moreover, Xu et al (2019) also published similar results related to functional biosynthesis antibiotic-related genes, such as PKSI, NRPS, ItuD, SrfC, and Sfp, by PCR from 33 different endophytic bacterial species, where 26 isolates from Bacillus ssp., showed antifungal activities against different phytopathogens of the mulberry plant respectively [25].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, after the amplification, we found that the majority of root-associated bacterial endophytes clearly displayed a positive indication regarding the 12 antibiotic-related genes. The findings of this study were supported by Kushwaha et al [24]. They described the PCR based amplification of antibiotic peptide related genes, including ItuD, BmyC, and srfA, from the 19 Bacillus endophytic bacterial strains with their biocontrol character in pearl millet cereal crop [24].…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations